Endoscopic ultrasound-guided through-the-needle microforceps biopsy in the evaluation of pancreatic cystic lesions: a multicenter study - Yang, Dennis (Endosc Int Open, 2018)
Background and study aims  Accurate diagnosis and classification of pancreatic cysts (PCs) remains a challenge. The aims of this study were to: (1) evaluate the safety and technical success of a novel microforceps for EUS-guided through-the-needle biopsy (TTNB) of PCs; and (2) assess its diagnostic yield for mucinous PCs when compared to FNA cyst fluid analysis and cytology. Patients and methods  This was a multicenter retrospective analysis of 47 patients who underwent EUS-FNA and TTNB for PCs between January 2014 and June 2017. Technical success was defined as acquisition of a specimen adequate for cytologic or histological evaluation. Cyst fluid carcinoembryonic antigen (CEA) was used to initially categorize cysts as non-mucinous (CEA < 192 ng/mL) or mucinous (CEA ≥ 192 ng/mL). Final diagnosis was based on identifiable mucinous pancreatic cystic epithelium on cytology, microforceps histology and/or surgical histology when available. Results  Forty-seven patients with PCs (mean size 30.7 mm) were included. TTNB was successfully performed in 46 of 47 (97.9 %). Technical success was significantly lower with FNA (48.9 %) compared to TTNB (85.1 %) ( P  < .001). For cysts with insufficient amount of fluid for CEA (n = 19) or CEA < 192 ng/mL, the cumulative incremental diagnostic yield of a mucinous PC was significantly higher with TTNB vs. FNA (52.6 % vs 18.4 %; P  = .004). TTNB alone (34.4 %) diagnosed more mucinous PCs than either CEA ≥ 192 ng/mL alone (6.3 %) or when combined with FNA cytology (9.4 %). One episode of self-limited bleeding (2.1 %) and one of pancreatitis (2.1 %) occurred. Conclusions  EUS-TTNB is safe and effective for evaluating PCs. TTNB may help increase the diagnostic yield of mucinous PCs.